POPULATION FLUCTUATION OF ADULT MALES OF THE FRUIT FLY, Bactrocera tau Walker (DIPTERA: TEPHRITIDAE) IN PASSION FRUIT ORCHARDS IN RELATION TO ABIOTIC FACTORS AND SANITATION - Hasyim, A.; ., Muryati; Kogel, W.J. de (Indonesian Journal of Agricultural Science, 2008)
Fruit fly (Bactrocera tau) is the most destructive pest on somefruits in Indonesia. Monitoring of the pest population is essentialas one of the procedures in the IPM concept. The studyaimed to investigate the seasonal fluctuation of adult males ofB. tau and their damage on passion fruits in relation to abioticfactors. The research was done by a survey method on threeplots of passion fruit orchards in Alahan Panjang, West Sumatra,Indonesia from March to December 2005. In plot 1 thefarmer practiced sanitation by removing damaged fruits andweeds from the orchard. In the plots 2 and 3 no sanitation waspracticed. Each plot was 1 ha in size. The parameters observedwere density of adult male B. tau and climatic factors (rainfallper day, number of rainy days, and average day temperature).Empty mineral water bottle traps were used to catch adult malesof B. tau. Each plot had 16 traps set up with cue lure as fruitfly attractant. Each trap was baited with 3 ml cue lure on acotton wick (1 cm diameter). The cotton wick was rebaited at2-week intervals. The traps were placed on host plants about1.5 m above the ground. Trapped flies were collected every twoweeks and counted. The data were analyzed by correlationanalysis. The results revealed that the number of male B. tauin three orchards showed a similar fluctuation during the studyperiod with a major peak in July. The lower numbers of fliescaptured in plot 1 (with sanitation) compared to the two otherplots (without sanitation) were consistent with a lower percentageof damaged fruits in the plot 1 compared to the other two.The percentage of damaged fruits gradually decreased over timeto about 20% in plot 1 which is lower than that in the other twoplots (30-40%). The number of fruit flies captured with cue lurebaited traps correlated positively with all three abiotic factorsstudied. The seasonal fluctuation of the fruit fly population andthe damage to the fruits are necessary to be studied as a procedurein IPM for controlling B. tau.